The results of the “My challenge” camp in addressing childhood obesity - Poklar Vatovec, Tamara (Zdravstveno varstvo, 2024)
Introduction: This article presents the development, implementation and results of the project “An interdisciplinary approach to the treatment of overweight children” under the name “My Challenge” camp. It is a 2-week multidisciplinary programme involving a physician, a dietitian, a psychologist, an occupational therapist or physiotherapist and a kinesiologist. The children stay in camp for 2 weeks and are actively involved in the daily preparation of healthy meals, participate in cooking workshops and interactive nutrition lessons, and are active outdoors throughout the programme. Methods: The study included 117 overweight or obese children, aged 7-18 years, 66 girls and 51 boys from ten camps between 2017 and 2023. Completed dietary questionnaires and anthropometric measurements were compared at baseline, after 2 weeks, and after 1 month. Results: Changes in children’s diets include an increase in meal frequency, in higher vegetables, fish, and seafood consumption, lower consumption of fried food and reduced consumption of sugary drinks. Boys more frequently consume fried food than girls and less frequently consume milk and dairy products. After one month, there was a decrease in body fat percentage, waist circumference and waist-to-height ratio in both genders. Conclusions: The “My Challenge” camp demonstrates promising outcomes in combating childhood obesity. Through a two-week multidisciplinary programme, significant improvements in dietary habits and anthropometric measures were observed. The findings underscore the importance of preventive education programmes for children in addressing the long-term health consequences of obesity. Further research and continued implementation of such initiatives are warranted to effectively tackle this public health issue.
Keywords: childhood obesity; debelost v otroštvu; diete; diets; food; health promotion; hrana; nutrition; overweight; prehrana; prekomerna telesna masa; spodbujanje zdravja